(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
University extension has evolved towards a dialogic and participatory model, including, among other aspects, the importance of local knowledge and resources. The project to valorize the “tomate platense” is analysed in order to investigate how university extension has impacted intangible dimensions (symbolic and subjective) of a specific reality. In particular, we reflect on a case of university intervention, highlighting how the perception of the “tomate platense” as a local product has been transformed, and the identity of the participating producers. Developed in the green belt of La Plata, Argentina, the project faced difficulties in overcoming commercialization challenges, affecting the economic viability of the proposal and remaining a marginal production. However, it succeeded in changing public perception and granting legitimacy and recognition to those who produced it.